Hubungan Pengetahuan Kandungan Merkuri dengan Keputusan Pembelian Produk Kecantikan pada Siswa Kelas XI SMK Negeri 27 Jakarta: Penelitian - Mutiah Azizah; Sri Irtawidjajanti; Neneng Siti Silfi Ambarwati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to see the relationship between knowledge of mercury content and purchasing decisions for beauty products in class XI students of SMK Negeri 27 Jakarta. The population and sample in this study were class XI students of the Beauty and Spa Program of SMK Negeri 27 Jakarta in the 2024/2025 school year who used beauty products as many as 66 students. The method used is quantitative associative with total sampling technique. Data were collected through an online questionnaire using a Guttman scale for the knowledge variable and a Likert scale for the purchasing decision variable. The results showed that students' knowledge level regarding mercury content was in the moderate category (72.7%) and the decision to purchase beauty products was also in the moderate category (43.9%). The Pearson correlation test resulted in a correlation value of -0.045 with a significance of 0.718 (p > 0.05), which indicates that there is no significant relationship between knowledge of mercury content and purchasing decisions. This finding indicates that students purchasing decisions are more influenced by other factors such as peer influence, trends, advertisements, not solely due to the level of knowledge about product content.